A Review on the Potency of Melaleuca leucadendron Leaves Solid Waste in Wood Preservation and Its In Silico Prediction upon Biological Activities - Christine Patramurti; Radjali Amin; Christofori M. R. R. Nastiti; Maywan Hariono (International Journal of Forestry Research)
The essential oils from cajuput leaves (Melaleuca leucadendron) have been well-known and applied, especially in healthcare management. However, the utilization of the leaves solid waste has not been explored and reported in detail. In this review, we elaborate on the cajuput leaves starting from the plant description and leaf morphology, chemical composition, biological activities, wood decomposing organism, and an in silico prediction upon its molecular mechanism. Based on the in silico prediction, compounds such as guaiol, lupene, and 1, 8-cineole have the potential to be antifungal and insecticide that associates with the cajuput potency as a wood preservative agent.